DAMPAK KEBIJAKAN HARGA PEMBELIAN PEMERINTAH TERHADAP PERMINTAAN DAN PENAWARAN GABAH DI DESA RIAS KECAMATAN TOBOALI KABUPATEN BANGKA SELATAN - Leta Nopriansyah; Fournita Agustina; Iwan Setiawan (Journal of Integrated Agribusiness, 2021)
Rias Village is one of the villages in the South Bangka Toboali Subdistrict which was established by the Bangka Belitung Provincial Government as a rice barn. The government through the South Bangka Regent chose Rias Village as an area of food security and planned to build an agricultural market as an effort to increase the welfare of citizens. This study aims to analyze the impact of the government's purchase price policy on grain demand and supply in Rias Village, Toboali Subdistrict, South Bangka Regency and analyze the effectiveness of government purchase price policies compared to government purchase price policies that previously applied to grain sales at farm level. This research was conducted in September 2018 until July 2019 in Rias Village, Toboali Subdistrict, South Bangka Regency. The research method used is the survey method. The sampling method used is quota sampling with samples of lowland rice farmers. The number of samples of paddy rice farmers is 98 people. Data analysis method uses qualitative analysis (Paired Sample t Test). The results of the study show the policy of purchasing government grain before 2015 and after 2015 through Presidential Regulation No.5 of 2015 did not have a significant impact or difference on the demand and supply of grain in the Rias Village of Toboali Sub-District. The policy of purchasing government grain through Presidential Regulation No.5 of 2015 gives a difference to the selling value of farmers despite a decline in production levels after 2015 due to pest and disease attacks on rice farmers so that the policy can be said to be effective and useful for farmers to guarantee prices grain at the farmer level.